In-service science teachers' readiness in teaching science subjects in english :a case study in UNIMAS - Jamilah, Jamil (Universiti Malaysia Sarawak, UNIMAS, 2009)
One of the most significant curricular changes in the Malaysian education system is the teaching of Science and Mathematics in English. After 39 years of teaching Science and Mathematics in first languages, making the transition to teach the same subjects in English poses many challenges to the teachers concerned. Thus, the Ministry of Education has provided them with professional development courses, in preparing them to stand and deliver in English competently. This study looks into the in-service Science teachers’ readiness in teaching Science subjects in English. This study aims to investigate how ready are the in-service teachers (who had been earlier trained to teach Science in BM or Mandarin) to teach Science in English after completing the PKPG degree course in UNIMAS. The participants of the study were the in-service Science teachers who are currently attending degree course in UNIMAS. A set of semistructures questions was utilised to find out (a) the participant experiences in teaching Science before attending the degree course, (b) how the course had prepared them to teach Science in English and (c) their readiness in meeting the challenges upon completion of their degree course. The data were qualitatively analysed into categories based on the responses gathered. A significant finding is that though the teachers clarified they were ready and had improved both in content subject and English proficiency; a small number mentioned the need for more assistance particularly in teaching and delivering Science subjects in English. The valuable information yielded by this study is expected to help Bahagian Pendidikan Guru (BPG), Ministry of Education (MoE) and the UNIMAS administration to develop programmes and strategies in accordance to the teachers’ needs to equip them well to teach Science subjects in English.